(untitled) (Journal of Naval Architecture and Marine Engineering, 2013)
Hull form optimization from a hydrodynamic performance point of view is an important aspect of ship design. This paper presents a computational method to estimate the ship resistance (viscous & wave) in calm-water. In the optimization process the evolution strategy (ES) technique is linked to the computational method to obtain an optimum hull form by taking into account the displacement as design constraint. For allowing the large variation of hull form during optimization process the hull surface is represented by NURBS. New hull forms are obtained from the well-known S60 hull and the classical Wigley hull taken as initial hulls in the optimization process at Fn=0.316. The optimization variables are a combination of ship hull offsets and main dimensions. The benchmark results for two test cases indicate that the total resistance of optimized hulls is reduced significantly. DOI: http://dx.doi.org/10.3329/jname.v10i1.12927